Intangible assets – Influence on the "return in equity on market value" (S&P100 Index) - Garcia, Jair (2020)
This study aims to analyze the effect of IA (exclusively those that are recognized and shown in the balance sheet) on the return on equity (ROE) using a market value approach. In order to analyze the influence of IA on ROE using market value, the study used components of the Standard and Poor 100 Index (S&P100). The S&P100 index comprises 101 companies across multiple industry groups; however, due to the research restrictions, only 68 companies were selected as the study’s sample. The research results were obtained using the Ordinary Least Square (OLS) method. The Pearson correlation test indicates a strong relationship of the IA to the ROE (excluding goodwill). According to our findings the influence of IA on ROEmv is 23% excluding goodwill. Additionally, the results indicated a significant gap between the models used. The limitations and future research directions are found at the bottom of the conclusion.